MOBILE TERRESTRIAL LASER SCANNER (TLS) ON-SITE PERFORMANCE EVALUATION METHOD AT PT AMMAN MINERAL NUSA TENGGARA - Daffa Aulia, Muhammad
Topographic mapping is crucial for the mining sector, especially open-pit mining. PT Amman Mineral Nusa Tenggara (AMNT), one of the largest mining companies in Indonesia, experiences rapid topographic changes due to high daily production rates. To address this, daily topographic mapping becomes essential. The Terrestrial Laser Scanner (TLS) has proven efficient, producing measurement data in the form of 3D point clouds. PT AMNT uses dynamic TLS, an advancement of TLS mounted on moving platforms. Continuous daily measurements can affect the performance of the dynamic TLS, necessitating an effective and efficient feasibility testing method. Annual calibration by the vendor often takes time, while the intensity of dynamic TLS usage at PT AMNT is very high. This proposal suggests an effective feasibility testing method for dynamic TLS as a system by comparing data from dynamic TLS with data from Static TLS and Electronic Total Station (ETS), which serves as the reference standard. The proposed product is a Standard Operating Procedure (SOP) outlining a structured and systematic feasibility testing procedure to assess the performance of dynamic TLS. This SOP involves the use of dynamic TLS, Static TLS, and ETS as validators.